Seriola aureovittata Temminck & Schlegel 1845 - Love, Milton S.; Bizzarro, Joseph J.; Cornthwaite, Maria; Frable, Benjamin W.; Maslenikov, Katherine P. (Zenodo, 2021)
** Seriola aureovittata Temminck & Schlegel 1845. Japanese Yellowtail Jack . In April 2015, 21 individuals of this species were recovered from a derelict Japanese vessel that had been damaged in the March 2011 tsunami (Craig et al. 2018). 193 cm (76 in) FL. Northwest Pacific Ocean. Both from Brown and Schofield (2020). Published as part of Love, Milton S., Bizzarro, Joseph J., Cornthwaite, Maria, Frable, Benjamin W. & Maslenikov, Katherine P., 2021, Checklist of marine and estuarine fishes from the Alaska-Yukon Border, Beaufort Sea, to Cabo San Lucas, Mexico, pp. 1-285 in Zootaxa 5053 (1) on page 155, DOI:10.11646/zootaxa.5053.1.1, http://zenodo.org/record/5578008